Increased photosensitivity at early growth as a possible mechanism of maize adaptation to cold springs. (2nd March 2019) - Grzybowski, Marcin; Adamczyk, Józef; Jończyk, Maciej; Sobkowiak, Alicja; Szczepanik, Jarosław; Frankiewicz, Kamil; Fronk, Jan; Sowiński, Paweł
Abstract: Maize is a cold-sensitive species, but selective breeding programs have recently succeeded in producing plants strikingly well adapted to the cold springs of a temperate climate, showing the potential for improved cold tolerance. The aim of the present study was to determine whether the adaptation of some inbred lines to spring chills is due to their increased true cold tolerance or whether it only represents an avoidance mechanism, which was the sole mode of adaptation during early stages of agricultural dispersal of maize towards higher latitudes. By characterizing numerous physiological features of several lines of different cold sensitivity, we show that a combination of both avoidance and tolerance is involved. A novel avoidance mechanism was found that favored unhindered development of the photosynthetic apparatus through protection of the shoot apex below soil level due to a shortened mesocotyl. It seems to be mediated by increased seedling photosensitivity at early growth stages. True tolerance involved improved protection of the cell membrane against cold injury at temperatures close to 0 °C and stimulation of light-induced processes (accumulation of anthocyanins, carotenoids, and chlorophyll, proper development of chloroplasts) at temperatures in the range of 10–14 °C, likely also related to the increased photosensitivity and mediated by gibberellin signaling. Abstract : High photosensitivity of seedlings of some modern maize inbred lines keeps the growing shoot below soil level and protects it against cold injury allowing for unhindered development at low temperatures.